2004
DOI: 10.1097/01.brs.0000143172.07771.fc
|View full text |Cite
|
Sign up to set email alerts
|

Fas-Ligand Expression on Nucleus Pulposus Begins in Developing Embryo

Abstract: The present results demonstrated that Fas ligand expression is not detected in the notochord, but at the time of intervertebral disc formation, Fas ligand expression develops in the nucleus pulposus. These results indicate that the immune privilege of the intervertebral disc may begin in the very early stages of disc formation. Moreover, Fas ligand may play an important role in the formation of the intervertebral disc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…29,30 Furthermore, the nucleus has been considered a relatively immune privileged site. 31 This is supported by our study in which the human bone marrow cells survived across a fully discordant barrier after xenogeneic transplantation for up to 42 days. The immune privileged characteristics are attributed to several factors.…”
supporting
confidence: 70%
“…29,30 Furthermore, the nucleus has been considered a relatively immune privileged site. 31 This is supported by our study in which the human bone marrow cells survived across a fully discordant barrier after xenogeneic transplantation for up to 42 days. The immune privileged characteristics are attributed to several factors.…”
supporting
confidence: 70%
“…An in vitro study further confirmed the activation of caspase-8 in cultured rabbit annulus fibrosus (AF) cells [33]. Recently, it has been suggested that FasL plays different roles in normal and degenerative IVDs [34], which helps the formation of immune privilege in normal IVDs [35][36][37], and triggerring apoptosis in IVDD [34]. Rannou et al [38] demonstrated that the mechanical overload-induced IVDD was mediated through the mitochondrial apoptotic pathway in IVD cells from human samples and mouse models.…”
Section: Introductionmentioning
confidence: 70%
“…We firstly evaluated the expression of fas and fasl in zebrafish whole embryos and larvae. The expression of fas and fasl in brain, eyes, gut and ovary of the adult fish is conserved in mammals, indicating a similar role for FAS/FASL during evolution [14, 40-43]. Interestingly, fasl expression is modulated during development while fas is expressed in all stages analyzed, suggesting the importance of a specific activation of this factor.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptotic process is involved in normal notochord development in Xenopus laevis [11], and in particular the extrinsic apoptotic pathway is conserved and necessary for notochord development in zebrafish [12]. In addition, the expression of tumor necrosis factor receptor (TNFR) FAS and its ligand FASL , leads to the notochord cells regression in the adult rat intervertebral disks [13, 14]. The autocrine-paracrine interaction between Fas and Fasl results in the trimerization and activation of the Fas receptor, which leads the cell to apoptosis [15, 16].…”
Section: Introductionmentioning
confidence: 99%